Answer:
[tex] g(x) = (x-2)^2 -6(x-2) +3[/tex]
[tex] g(x) = x^2 -4x +4 -6x +12 +3[/tex]
[tex] g(x) = x^2 -10 x +19[/tex]
[tex] g(x) = x^2 -10 x + 25 +19 -25[/tex]
[tex] g(x) = (x-5)^2 -6[/tex]
[tex] y= (x-h)^2 -kk[/tex]
Where h,k represent the vertex and we got:
[tex] (h,k)= (5,6)[/tex]
(5,6)
Step-by-step explanation:
We have this original function given :
[tex] f(x) = x^2 -6x +3[/tex]
And we want to find the vertex for this new function [tex] g(x) = f(x-2)[/tex] and we have:
[tex] g(x) = (x-2)^2 -6(x-2) +3[/tex]
And solving the square we got:
[tex] g(x) = x^2 -4x +4 -6x +12 +3[/tex]
And adding similar terms we got:
[tex] g(x) = x^2 -10 x +19[/tex]
Now we can complete the square like this:
[tex] g(x) = x^2 -10 x + 25 +19 -25[/tex]
[tex] g(x) = (x-5)^2 -6[/tex]
The general equation is given by:
[tex] y= (x-h)^2 -kk[/tex]
Where h,k represent the vertex and we got:
[tex] (h,k)= (5,6)[/tex]
(5,6)